2011
DOI: 10.1523/jneurosci.6546-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Astroglial Apolipoprotein E and Liver X Receptor-α Expression for Microglial Aβ Phagocytosis

Abstract: Liver X receptors (LXRs) regulate immune cell function and cholesterol metabolism, both factors that are critically involved in Alzheimer's disease (AD). To investigate the therapeutic potential of long-term LXR activation in amyloid-␤ (A␤) peptide deposition in an AD model, 13-month-old, amyloid plaque-bearing APP23 mice were treated with the LXR agonist TO901317. Postmortem analysis demonstrated that TO901317 efficiently crossed the blood-brain barrier. Insoluble and soluble A␤ levels in the treated APP23 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 50 publications
(66 reference statements)
2
115
0
Order By: Relevance
“…In these studies the LXR-agonist T0901317 was able to cross the BBB in vivo and reduce Aβ burdens in mouse brain tissue, however spatial learning only showed little improvement [123]. This was correlated with an increased ABCA1 expression in astrocytes [123] and in neuronal cells [122].…”
Section: Alzheimer's Diseasementioning
confidence: 91%
See 2 more Smart Citations
“…In these studies the LXR-agonist T0901317 was able to cross the BBB in vivo and reduce Aβ burdens in mouse brain tissue, however spatial learning only showed little improvement [123]. This was correlated with an increased ABCA1 expression in astrocytes [123] and in neuronal cells [122].…”
Section: Alzheimer's Diseasementioning
confidence: 91%
“…In these studies the LXR-agonist T0901317 was able to cross the BBB in vivo and reduce Aβ burdens in mouse brain tissue, however spatial learning only showed little improvement [123]. This was correlated with an increased ABCA1 expression in astrocytes [123] and in neuronal cells [122]. The key role played by ABCA1 in the pathogenesis of AD was reported earlier by Koldamova and colleagues (2005 [124]) who demonstrated that APP23 mice lacking abca1 exhibit increased amyloid deposition compared to control animals.…”
Section: Alzheimer's Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…Just like microglia, astrocytes express intra-and extracellular Aβ-degrading enzymatic apparatus upon exposure to Aβ [164]. Furthermore, they also internalize and degrade Aβ, with astroglial ApoE playing crucial roles in both astroglia-and microgliamediated Aβ clearance among experimental conditions [165][166][167][168]. Supporting a potential detrimental role of astrocytes upon chronic activation during AD pathogenesis, viral inactivation of astrocytes alleviated the pathology in a transgenic murine model of AD [169].…”
Section: Neuroinflammation In Alzheimer's Diseasementioning
confidence: 98%
“…Sporadic AD is strongly associated with apolipoprotein E ε4 (APOE4) expression, whereas APOE2 expression is protective (44). Astrocytes and microglia express APOE under the control of nuclear hormone receptors, and it plays an important role in Aβ phagocytosis by microglia (45), although it may influence AD through multiple mechanisms. The balance between Aβ production and removal seems to determine amyloid burden in AD brain (46), and dysregulated Aβ clearance rather than increased Aβ production has been linked to the etiology of sporadic AD (47).…”
Section: Beyond M1 and M2 Classificationmentioning
confidence: 99%